Imunoensaio de fluxo lateral para diagnóstico de tuberculose - Silva, Vinicius Cauan Mendes da (Universidade Federal de São Carlos, 2022)
Tuberculosis is the leading cause of death among infectious diseases, according to the World Health Organization, and represents a major public health problem. About 1.4 million people died from tuberculosis worldwide in 2019, with about 4,500 cases per year in Brazil since 2010. Early diagnosis of tuberculosis is essential for treatment to be more efficient, avoiding nonspecific therapies that contribute to the emergence of resistant forms of the pathogen. Current diagnostic methods, such as immunoassays and molecular tests, require infrastructure and specialized professionals, compromising diagnosis in low-resource settings. In this sense, new biomarkers have been researched for the development of new diagnostic tools. Among these biomarkers, we have the Hsp65 and CFP-10 proteins, which are found in different samples from tuberculosis patients and are secreted in the early stages of infection. Therefore, the present study presents the development of a paper-based immunosensor for the simultaneous detection of Hsp65 and CFP-10 proteins using a lateral flow system. For this, the biomarkers were immobilized on the nitrocellulose membrane for detection through the competitive model, in a device composed of the sample, detection, and absorption zone. Gold nanoparticles were functionalized with antibodies against the targets to act as detection labels. After optimizing the immunosensor in different experimental parameters, such as sample volume and incubation time, it was possible to build calibration curves for both biomarkers for the concentration range of 2.5 μmol.L-1 and 40 μmol.L-1 . The device presented several advantages over the diagnostic methods already used, such as low-cost, easy-to-use, fast results detectable with the naked eye, providing a promising tool for the diagnosis of tuberculosis at the point of care.
Lateral flow immunoassay for diagnosis of tuberculosis
Keywords: Tuberculosis; Rapid diagnosis; Imunossensor; Paper; Lateral flow; Biomarkers; Hsp65; CFP-10; Tuberculose; Diagnóstico rápido; Imunossensor; Papel; Fluxo lateral; Biomarcadores; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::PROP.OTICAS E ESPECTROSC.DA MAT.CONDENS;OUTRAS INTER.DA MAT.COM RAD.E PART.